Pemberdayaan Masyarakat melalui Pertanian Organik: Sosialisasi dan Implementasi di Desa Besakih, Karangasem - Dayanti, Made Ari Riska; Suprianingsih, Ni Wayan; Sutasoma, I Wayan Gede; Prakasa, I Made Panji Tirta (UNIVERSITAS INDO GLOBAL MANDIRI, 2025)
This program focuses on enhancing the understanding, skills, and participation of the Besakih Village community, Rendang District, Karangasem Regency, in implementing organic farming systems, particularly in the cultivation of aloe vera. The focus emerged from the low level of awareness and capability among farmers in applying Standard Operating Procedures (SOPs) for organic farming, which play a crucial role in maintaining environmental sustainability and improving agricultural productivity. The program was designed as a strategic effort to promote environmentally friendly and sustainable plantation management by reducing dependence on chemical fertilizers and pesticides, in collaboration with a private company in the food manufacturing sector, PT. Alove Bali Ind. The activities were conducted in three main stages: education, implementation, and evaluation. The education stage emphasized the dissemination of organic farming benefits and the introduction of aloe vera cultivation SOPs facilitated by PT. Alove Bali Ind. The implementation stage involved direct field assistance to ensure the effective application of land transfer, composting, and plant rejuvenation practices. The evaluation stage was carried out collaboratively among academics, industry partners, and the community to identify challenges and formulate sustainable solutions. Farmer empowerment in adopting organic farming practices increased by approximately 71%, leading to greater income stability and growth within the community. This program serves as an effective model of cross-sector collaboration in developing an environmentally based community empowerment initiative that can be replicated in other regions with similar agricultural potential.